Determination and Quantitative Analysis of Fatty Acids from Hippophae rhamnoides L. Using Reversed-Phase HPLC with Fluorescence Detection and Atmospheric Chemical Ionization-Mass Spectrometry - Hu1, Na; Ji1, Zhongyin; Wang1, Aihong; Han1, Lijuan; You1, Jinmao; Suo1, Yourui (Asian Journal of Chemistry, 2014)
In the present study, a selective and sensitive method using 2-(11H-benzo[a]carbazol-11-yl) ethyl 4-methylbenzenesulfonate as labeling reagent based on pre-column derivatization for the quantitative analysis of fatty acids was developed and validated. The results indicated the proposed method exhibited excellent selectivity, sensitivity, reproducibility and applicability. Good linear correlations were obtained for each fatty acid with correlation coefficients greater than 0.9994. The values of LOQs and LODs ranged from 1.34 to 6.64 ng mL-1 and 0.42 to 1.82 ng mL-1, respectively. This method was successfully employed to analyze fatty acid composition in the seeds of Hippophae rhamnoides L. The results showed that seeds of Hippophae rhamnoides L. seeds are rich in fatty acids and the contents of unsaturated fatty acids are much higher than that of saturated fatty acids. In addition, the contents of total fatty acids, unsaturated fatty acids and each fatty acid are various among different origins. The analysis of fatty acids in seeds of Hippophae rhamnoides L. is important to the pharmacological research of Hippophae rhamnoides L.